Marketing Strategies in Increasing Sales of 136 Roastery & Coffeeshop in East Java - Wulandari, Lia; Palupi, Anistya; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Coffee is a drink that comes from roasted and processed coffee beans, has global appeal with a variety of types, flavors and brewing methods. Coffee beans are obtained from coffee berries that grow mainly in tropical areas, such as Malang City, East Java, which is known for its moderate humidity level and average temperature of 27°C, giving coffee from this area a special taste. With the times, coffee shops have become popular places to enjoy coffee and work. 136 Roastery & Coffeeshop, seeing opportunities in the rapidly growing coffeeshop industry in Indonesia, especially in East Java, decided to invest in a roaster machine. This research is a response to the company's efforts to increase sales using various methods to achieve and increase profits. By facing various obstacles and weaknesses, companies innovate according to current developments to have characteristics that differentiate them from competitors. This research aims to evaluate the strengths and weaknesses of the marketing strategies implemented by 136 Roastery & Coffeeshops in East Java. Qualitative research methods using primary and secondary data, involving interviews and documentation, show that companies can increase sales by implementing marketing strategies using the 7P Marketing Mix and SWOT Analysis.